Cardiovascular Physiology at High Altitude. Issue 1 (1st March 2011) - Hooper, T; Mellor, Adrian
Abstract : The role of the cardiovascular system is to deliver oxygenated blood to the tissues and remove metabolic effluent. It is clear that this complex system will have to adapt to maintain oxygen deliver in the profound hypoxia of high altitude. The literature on the adaptation of both the systemic and pulmonary circulations to high altitude is reviewed.